Efeito da atividade física na sensibilidade à insulina e no sinal insulínico em ratos com doença periodontal - Mota, Max Sander de Oliveira da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Studies have shown that there is a correlation between Diabetes Mellitus (DM) and Periodontal Disease (PD) in a way that people with DM present higher prevalence and severity of PD, when compared with healthy people. It is also observed that among people with PD there is an increased prevalence of Diabetes. Previous studies in our laboratory showed that PD induces alterations in insulin signaling and insulin resistence. Several studies showed that exercise can promote improvements in insulin sensitivity. Knowing that DP reduces insulin sensitivity and signaling, this study investigated if physical exercise can revert or improve this condition in rats with PD. Therefore, it was assessed in rats with PD submitted or not to exercise: 1) insulin sensitivity; 2) glycemia, insulinemia; 3) TNF-α and IL-6 plasma levels; 4) cholesterolemia and triglyceridemia; 5) insulin receptor substrate pp185 (IRS-1/IRS-2) tyrosine and serine phosphorylation status. Therefore, 80 male Wistar rats (two-month-old) were distributed into four groups: 1) sedentary control group without PD (CNS); 2) exercised control group without PD (CNEx); 3) sedentary group with PD (DPS); 4) exercised group with PD (DPEx). In those groups with PD, the disease was induced by ligating silk thread on the lower first molars. After that, it was assessed food ingestion (three times a week) and body weight (once a week) of rats in all groups. In the 28th day after the disease induction, the resistance training began. After 12 weeks of training, the experiments were performed. Statistical analysis was performed by analysis of variance (ANOVA) followed by Tukey's test. Significance value adopted was of 5%. No significant difference was observed in glycemia of the studied groups. DPS had higher insulin levels when compared to CNS, CNEx and DPEX. DPS showed increased insulin...

Estudos têm demonstrado que existe uma correlação entre diabetes mellitus (DM) e doença periodontal (DP) de tal maneira que pessoas com DM apresentam uma maior prevalência e severidade da doença periodontal, quando comparadas com pessoas saudáveis. Ademais, verifica-se também que entre pessoas com DP, há uma maior incidência de diabetes. Estudos anteriores do nosso laboratório demonstraram que a DP induz alteração no sinal insulínico e resistência à insulina. Vários estudos evidenciaram que o exercício físico promove melhora na sensibilidade à insulina. Sabendo-se que a DP reduz a sensibilidade insulínica e o sinal insulínico, este trabalho procurou averiguar se o exercício físico consegue reverter ou melhorar esse quadro em ratos com DP. Portanto, foram avaliados em ratos com DP, submetidos ou não ao exercício: 1) sensibilidade à insulina; 2) glicemia, insulinemia; 3) concentração plasmática de TNF-α e IL-6; 4) colesterolemia e trigliceridemia; e 5) grau de fosforilação em tirosina e serina do substrato do receptor de insulina pp185 (IRS-1/IRS-2). Para tanto, 80 ratos Wistar (2 meses de idade) foram distribuídos em quatro grupos: 1) grupo controle sedentário sem DP (CNS); 2) grupo controle exercitado sem DP (CNEx); 3) grupo sedentário com DP (DPS); 4) grupo exercitado com doença periodontal (DPEx). Nos grupos com DP, esta doença foi induzida por meio da ligadura com fio de seda ao redor do 1º molar inferior. Após a colocação da ligadura foram avaliadas, três vezes por semana, a ingestão de ração e, uma vez por semana, o peso corporal dos ratos. No vigésimo oitavo dia após a indução da doença foi iniciado o treinamento resistido. Após 12 semanas de treinamento físico, os experimentos foram realizados. A análise estatística foi realizada pela análise de variância (ANOVA) seguida do teste...
Keywords: Periodontite; Resistência à insulina; Diabetes; Inflamação; Proteínas substratos do receptor de insulina; Exercicios; Periodontitis